2022
DOI: 10.21203/rs.3.rs-1364774/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitudes and perceptions of sexual and reproductive health rights among undergraduates in state universities in Sri Lanka

Abstract: Introduction: Sexual and Reproductive Health Rights (SRHR) are universal. The objective was to describe the knowledge and attitudes and explore the perceptions regarding SRHR among undergraduates. Methods: A cross sectional study was conducted among 1575 undergraduates using stratified cluster sampling of the selected universities. A pre-tested self-administered questionnaire was administered to assess knowledge and attitudes on SRHR. In addition, focus group discussions were conducted to explore perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(4 reference statements)
1
0
0
Order By: Relevance
“…Since our ndings revealed that only 43% have good knowledge of SRH; hence UR students need to increase their knowledge of SRHR. These ndings are almost similar to various studies conducted in Ethiopia, India and Sri Lanka(Gebresilassie et al,2019;Gajendran, 2020;Perera & Abeysena 2022). knowledge about SRHR is essential, studies argue that youths face an increased risk of unwanted pregnancy, STIs, and HIV/AIDS.…”
supporting
confidence: 87%
“…Since our ndings revealed that only 43% have good knowledge of SRH; hence UR students need to increase their knowledge of SRHR. These ndings are almost similar to various studies conducted in Ethiopia, India and Sri Lanka(Gebresilassie et al,2019;Gajendran, 2020;Perera & Abeysena 2022). knowledge about SRHR is essential, studies argue that youths face an increased risk of unwanted pregnancy, STIs, and HIV/AIDS.…”
supporting
confidence: 87%